Treatment of cellulite based on the hypothesis of a novel physiopathology - Pereira de Godoy JM; de Fátima Guerreiro de Godoy M (Dove Medical Press, 2011)
José Maria Pereira de Godoy1, Maria de Fátima Guerreiro de Godoy21Department of Cardiology and Cardiovascular Surgery, 2Lymphovenous Rehabilitation, FAMERP, São José do Rio Preto, BrazilBackground: The aim of the current study is to report on a new form of treatment for cellulite based on a novel physiological hypothesis.Methods: A novel treatment for cellulite was evaluated in 14 patients aged 19–36 (mean 27.5) years. The only inclusion criterion was clinically diagnosed cellulite, and the exclusion criteria were history of edema, obesity, or any other disease diagnosed during the physical examination. Perimetry was performed at the gluteal fold, at 5 cm and 10 cm below the gluteal fold for both legs, and 5 cm and 10 cm below the navel. Additionally, standard photographs were taken and a questionnaire of satisfaction was applied. The patients were submitted to a treatment regimen of 1.5 hours per day adapted for the treatment of cellulite, consisting of manual and mechanical lymph drainage and cervical stimulation using the Godoy and Godoy technique. After 10 sessions over two weeks, the patients were evaluated again.Results: Reductions were identified at both points below the navel, the points on the thighs, and at the gluteal fold (P < 0.0001).Conclusion: This technique of lymphatic system stimulation is efficacious in the treatment of cellulite.Keywords: cellulite, treatment, physiopathology